Turbulent dissipation along contrasting internal tide paths off the Amazon shelf from AMAZOMIX - F. Kouogang; F. Kouogang; A. Koch-Larrouy; J. Magalhaes; A. Costa da Silva; D. Kerhervé; A. Bertrand; E. Cervelli; F. Assene; F. Assene; J.-F. Ternon; P. Rousselot; et al. (Ocean Science)
The Amazon shelf break is a key oceanic region where strong internal tides (ITs) are generated, playing a substantial role in climate processes and ecosystems through vertical dissipation and mixing. During the AMAZOMIX survey (2021), currents, hydrography, and turbulence were measured over the M2 tidal period (12.42 h) at multiple stations along both high (HTE) and low (LTE) tidal energy paths, covering IT generation and propagation regions off the Amazon shelf. This dataset provides a unique opportunity to assess IT-driven vertical dissipation and quantify its spatial extent and influence in the region.